What works? evidence-based policy and practice in public services - Davies, Huw T. O. 1961-; Nutley, Sandra ca. 20./21. Jh; Smith, Peter 1952- (The Policy Press, 2000)
This book provides a timely and novel contribution to the debate surrounding the role of 'evidence' in specific public policy areas. It explores the creation, dissemination and use of evidence within the areas of healthcare, education, criminal justice, social care, welfare, housing, transport and urban renewal
Title from publisher's bibliographic system (viewed on 14 Sep 2022)
Keywords: County services / Great Britain; Municipal services / Great Britain